Fermi large area telescope study of cosmic rays and the interstellar medium in nearby molecular clouds - Ackermann, Markus; Grondin, Marie-Hélène (The astrophysical journal, 2012)
We report an analysis of the interstellar γ-ray emission from the Chamaeleon, R Coronae Australis (R CrA), and Cepheus and Polaris flare regions with the Fermi Large Area Telescope. They are among the nearest molecular cloud complexes, within 300 pc from the solar system. The γ-ray emission produced by interactions of cosmic rays (CRs) and interstellar gas in those molecular clouds is useful to study the CR densities and distributions of molecular gas close to the solar system. The obtained γ-ray emissivities above 250 MeV are (5.9 ± 0.1 stat +0.9 -1.0sys ) × 10 -27 photons s -1 sr -1 H-atom -1 , (10.2 ± 0.4 stat +1.2 -1.7sys ) × 10 -27 photons s -1 sr -1 H-atom -1 , and (9.1 ± 0.3 stat +1.5 -0.6sys ) × 10 -27 photons s -1 sr -1 H-atom -1 for the Chamaeleon, R CrA, and Cepheus and Polaris flare regions, respectively. Whereas the energy dependences of the emissivities agree well with that predicted from direct CR observations at the Earth, the measured emissivities from 250 MeV to 10 GeV indicate a variation of the CR density by 20% in the neighborhood of the solar system, even if we consider systematic uncertainties. The molecular mass calibrating ratio, X CO = N (H 2 )/ W CO , is found to be (0.96 ± 0.06 stat +0.15 -0.12sys ) × 10 20 H 2 -molecule cm -2 (K km s -1 ) -1 , (0.99 ± 0.08 stat +0.18 -0.10sys ) × 10 20 H 2 -molecule cm -2 (K km s -1 ) -1 , and (0.63 ± 0.02 stat +0.09 -0.07sys ) × 10 20 H 2 -molecule cm -2 (K km s -1 ) -1 for the Chamaeleon, R CrA, and Cepheus and Polaris flare regions, respectively, suggesting a variation of X CO in the vicinity of the solar system. From the obtained values of X CO , the masses of molecular gas traced by W CO in the Chamaeleon, R CrA, and Cepheus and Polaris flare regions are estimated to be 5 × 10 3 M ☉ , 10 3 M ☉ , and 3.3 × 10 4 M ☉ , respectively. A comparable amount of gas not traced well by standard H I and CO surveys is found in the regions investigated.
Gesehen am 05.11.2018